Computational Pharmacology Approach to Identify Antidiarrheal Candidates from Eleusine indica L.: Molecular Docking Simulation and Drug-likeness Prediction Targeting 5ZHP Receptor - Faisal Akhmal Muslikh; Rizki Rahmadi Pratama; Syahputra Wibowo; Yanu Andhiarto; Burhan Ma’arif; Maximus M. Taek (Journal Medical Informatics Technology, 2026)
Diarrhea remains a significant global health concern with high morbidity and mortality rates, particularly in developing countries. The use of synthetic antidiarrheal drugs is associated with various adverse effects, necessitating the exploration of safer therapeutic alternatives derived from natural sources. This study aimed to evaluate the potential of secondary metabolite compounds from Eleusine indica as antidiarrheal candidates through an in silico approach, employing drug-likeness analysis and molecular docking simulation against the muscarinic acetylcholine M3 receptor (PDB ID: 5ZHP). Drug-likeness analysis was performed using the SwissADME web tool based on Lipinski's Rule of Five. Molecular docking simulation was conducted using Molegro Virtual Docker, with the root mean square deviation (RMSD) value employed as a validation parameter. The results revealed that the majority of the compounds satisfied Lipinski's criteria, indicating their potential as oral drug candidates. Docking method validation yielded an RMSD value of 0.777437 Å, confirming the validity and reliability of the docking procedure. Docking results suggested that compound M15 (andrographolide) and compound M13 [4-(1-hydroxyethyl)-2,6-bis(3-methylbut-2-en-1-yl)phenol] exhibited the lowest Rerank Scores of −116.686 and −114.300, respectively, which were notably lower than that of the positive control loperamide (−41.9287), suggesting potentially stronger binding affinity and more favorable interaction with the target receptor. However, these findings are predictive in nature and require further validation through experimental biological studies and molecular dynamics simulations to confirm actual binding stability and pharmacological effectiveness.